A case of presumed herpes keratouveitis in a patient treated with fingolimod. (3rd June 2016) - Ayers, Malissa C; Conway, Devon S
We discuss a case of presumed bilateral herpes simplex keratouveitis in a 36-year-old multiple sclerosis patient switched to fingolimod from glatiramer acetate. Fingolimod treatment appears to increase the risk of herpesvirus infections, including with herpes simplex virus and varicella zoster virus. This case report reviews the potential immunology behind this risk, and identifies the need for further research, including ways to minimize and stratify risk for herpesvirus reactivation.